Legal Certainty on the Implementation of Post Mining Land Reclamation of Unlicensed Coal Mining as an Effort to Preserve the Environment in Indonesia - Sonda, Suarni; Alqadri, Dinar; Reumy, Ludia Jemima I.R.; Bym, Ernita Rahmadhani; Fahd, Abo (Universitas Negeri Semarang, 2025)
Indonesia, as a country with potential natural resources such as coal, faces major challenges in tackling the negative impacts of unlicensed coal mining, including weak post-mining land reclamation. This research aims to examine government policies to overcome the problem of reclamation of unlicensed coal mines in Indonesia. The research method used qualitative research with a focus on analyzing regulations and cases of unlicensed coal mining. The results show that various government policies related to mine reclamation are regulated in laws and regulations. Still, the reclamation of unlicensed mines or illegal mines is not clearly regulated. However, it can be prosecuted as corruption crimes because it is considered detrimental to the state or becomes the responsibility of the government if the perpetrator is unknown; this adds to the problem of carrying out reclamation considering the large number of coal mining pits so that the government is difficult to carry out reclamation. Not only that, law enforcement against the implementation of unlicensed mining is still not optimal; existing regulations emphasize criminal sanctions and fines more than reclamation responsibilities. These findings indicate the need for government policies in the coal mining sector that emphasize legal certainty regarding the responsibility of coal mining actors who do not have permits or the government’s responsibility in carrying out reclamation needs to be strengthened by adding policies for reclamation of unlicensed mining land and more effective supervision and application of sanctions that emphasize reclamation responsibilities in order to achieve the goal of environmental sustainability.